Ludmila Wegenerova-Salmonova 1897-1968 (1999) - Dolezalova, Kristyna (Iluminace, 2018)
Through a description of the archive collection stored at the National Film Archive, the text reconstructs the life and career of actress Ludmila Wegenerova-Salmonova, who, despite her Czech origins, became famous exclusively in German silent cinema alongside Paul Wegener, before returning to Prague after the war to work as a teacher.
Keywords: Ludmila Wegenerova-Salmonova; Paul Wegener; German silent film; National Film Archive; archive collection